Child development in psychology training: An analysis of scientific production in course conclusion works (Research, Society and Development, 2025)
Child development is a fundamental part of training in Psychology, being crucial to understanding the affective, cognitive, motor and social processes that characterize childhood. The objective of this article is to present a study on child development in Psychology training. This study uses a qualitative approach with a bibliometric focus, aiming to map and analyze the scientific production on child development in the Course Completion Works (TCC) of Psychology students. The research was conducted based on recognized national journals, between the years 2014 and 2024, applying selection criteria and specific keywords. Despite the importance of the topic in academic training, there was a lack of studies that directly connect child development to the process of preparing the TCC, revealing a notable gap in the literature. This absence not only suggests an epistemological void, but also indicates weaknesses in the connection between theory and practice in undergraduate Psychology. The results highlight the need to rethink pedagogical methodologies, promoting active practices, meaningful learning and critical praxis, in order to provide more integrated and contextualized training.